THE EFFECTIVENESS OF TIK-TOK BUZZ MARKETING IN INCREASING SALES OF BAKSO MASROY SURABAYA - Asy’ad Al Jihadi; Didik Hariyanto (Antis Publisher, 2024)
General Background: The rise of social media has transformed marketing practices, with platforms like TikTok emerging as influential tools for businesses, particularly in the culinary sector. Specific Background: This research investigates the buzz marketing strategy employed by Masroy Surabaya to enhance sales of its meatballs through TikTok, targeting the platform’s extensive user base. Knowledge Gap: While existing literature acknowledges the potential of social media in marketing, there is limited empirical analysis on the specific impact of TikTok buzz marketing on sales in local food businesses. Aims: This study aims to evaluate the effectiveness of TikTok as a medium for buzz marketing and its influence on the sales performance of Masroy Surabaya meatballs. Results: Utilizing a qualitative descriptive approach with data gathered from in-depth interviews and content analysis involving ten TikTok users who are also consumers of Masroy meatballs, the findings indicate that engaging and creative content significantly enhances brand awareness and motivates consumer trials. The buzz marketing strategy has demonstrably contributed to increased sales. Novelty: This research offers novel insights into the effective utilization of TikTok for culinary marketing, illustrating how specific content strategies can drive consumer engagement and sales in local markets. Implications: The results underscore TikTok's potential as a powerful promotional tool, suggesting that local businesses can leverage innovative social media strategies to enhance their marketing mix, particularly in product quality, pricing, placement, and promotional efforts. This study not only fills a critical gap in the literature but also provides practical recommendations for culinary marketers.